A study on color visual perception of museum exhibition space based on eye movement experiments - Hu, Linhui; Li, Jinxiao; Chen, Lidan; Shan, Qian; Jin, Yu; Ren, Guangpei (Frontiers in Psychology, 2024)
Color is an essential element in the exhibition space of museums, influencing people’s visual experience. To quantitatively study the relationship between color and individual visual perception in museum exhibition spaces, the study used eye-tracking technology combined with a questionnaire, exploring the relationship between color and visual perception in the exhibition environments of history museums in terms of hue, saturation, and brightness of color. Taking the Ruijin Central Revolutionary Base in Jiangxi Province as a historical display space for research, the results show that when the saturation is 69–77%, or the hue is red (0°H), the exhibited. environments have stronger color attractiveness. The study demonstrated that the first fixation duration in eye movement data significantly negatively correlates with the subject’s personal preference, comfort, pleasure, and attractiveness. Researchers can use this as an evaluation parameter for visual perception of exhibition space.